Case report: Local and systemic combination therapy: endoscopic injection of an oncolytic virus with PD-1 inhibitor for an elderly patient with advanced gastrointestinal cancer - Luo, Siqi; Ding, Xue; Zhang, Hong; Dai, Li; Zhang, Meifeng; Wang, Zhengye; Xu, Liangbi; Wang, Qian; Jin, Xiangren (Frontiers in Immunology, 2025)
Gastric and colorectal cancers present significant therapeutic challenges, particularly in the elderly population, who often have comorbidities and diminished tolerance to standard treatments. This report describes an 85-year-old male with concurrent stage III gastric adenocarcinoma and stage IIIb microsatellite stable colorectal cancer, who declined both surgery and chemotherapy. Subsequently, the patient was treated with an innovative regimen consisting of endoscopic intratumoral injections of Oncolytic adenovirus H101 in combination with the PD-1 inhibitor tislelizumab. Following this combined therapeutic approach, the patient demonstrated notable tumor shrinkage and downstaging, accompanied by a reduction in serum tumor markers, including CEA and CA19-9. Additionally, there was an observed increase in CD8+ and CD4+ T-cell counts, indicating systemic immune activation. The treatment was well-tolerated, with the only reported adverse event being mild fever. The patient achieved nearly 4 months of progression-free survival and a substantial improvement in quality of life. This case highlights the potential of combining oncolytic virotherapy with PD-1 inhibition as a promising and novel personalized strategy for treating elderly patients with advanced gastrointestinal cancers who are unsuitable candidates for conventional therapies.